Detection of Gelatin Origin Using Fourier Transform Infrared Spectroscopy and High Performance Liquid Chromatography - Rusli, Norakasha (2011)
A study on detection of gelatin origin was conducted. Rapid method was developed using Fourier transform infrared (FTIR) spectroscopy to distinguish between bovine and porcine gelatin. The results showed that FTIR spectroscopy was capable of distinguishing bovine and porcine gelatin by analyzing the region between 3290- 3280 cm-1 and 1660-1200 cm-1 using discriminant analysis (DA). The Cooman’s plot clearly showed that both gelatins were classified according to their respective group. The subsequent study explains the application of high performance liquid chromatography (HPLC) in ascertaining the source of gelatin using amino acid analysis. A partial least square (PLS) calibration demonstrated good linear regression (R2) of 0.991 and 0.983 for Sigma and Merck gelatin standards, correlation between actual values against predicted data obtained from the cross-validation of gelatin mixture. Three major amino acids namely glycine (Gly), proline (Pro) and hydroxyproline (Hyp) were applied in principal component analysis (PCA) and the score plots obtained show good separation between pure bovine, pure porcine or the mixture of bovine and porcine gelatin for both Sigma and Merck standards. Finally, the third study was conducted to know the capabilities of these detection methods to be applied in real food samples. Market samples were analyzed by both FTIR spectroscopy and amino acid analysis. Results presented by Cooman’s plot and PCA proved that the samples were distinctly divided in two groups accordingly depending on their source without any confusion or mistake. However, the analysis cannot be done for the samples containing added ingredients such as flavouring and colouring. In conclusion, this study provides methods for determining the source of gelatin focused on bovine and porcine. These methods are suitable to be use in the analysis of halal food authentication.